Sistem Otomatis Pengisian Water Truck Pada Area Waterfill di Pertambangan Batubara : Automatic System Filling Water Truck on Waterfill Area in Coal Mining - Rahmat Meygi Syafalaah; Paramytha, Nina (Jurnal Teknik Elektro dan Komputer, 2024)
Abstract — At PT. Darma Henwa Asam-Asam Coal Project site, the water truck unit operator must get off to start the waterfill engine to fill the water in the Water Truck unit tank, so it takes quite a long time and has the potential for accidents to the operator when getting on and off to start the engine. The development of the system aims to increase efficiency and reduce water filling time. This study involved solar panels, batteries, HC-SR04 ultrasonic sensors, E18-D80NK infrared sensors, Arduino Uno R3, and others. The study results showed that this automatic system can detect water trucks and fill water efficiently. Testing was carried out with two water truck objects with a capacity of 1000 ml and 500 ml with a filling duration of 9 seconds and 5 seconds respectively. This system is also equipped with a monitoring mechanism that is displayed on the display and a full charge indicator using a buzzer. Measurements and tests showed a percentage of error in the battery component of 27% compared to the datasheet, but other elements were within the appropriate range. The effectiveness of the solar panel was tested with a peak power of 5.5 watts in sunny conditions. Battery testing for 120 minutes showed a Depth Of Discharge of 42%, maintaining good battery life. This automated system can improve operational efficiency and reduce safety risks due to manual charging. This research provides an important contribution to applying automation technology in the mining industry. Key words—Water Filling Efficiency; Infrared Sensor; Ultrasonic Sensor; Automatic System; Water Truck   Abstrak —  Pada PT. Darma Henwa site Asam-Asam Coal Project, operator unit water truck harus turun untuk menghidupkan engine waterfill dalam pengisian air di tangki unit Water Truck, sehingga memerlukan waktu yang cukup lama juga berpotensi terjadi kecelakaan terhadap operator ketika naik-turun untuk menghidupkan engine. Pengembangan sistem bertujuan untuk meningkatkan efisiensi dan mengurangi waktu pengisian air. Penelitian ini melibatkan panel surya, battery, sensor ultrasonik HC-SR04, sensor inframerah E18-D80NK, Arduino Uno R3, dan lainnya. Hasil penelitian menunjukkan sistem otomatis ini dapat mendeteksi water truck dan mengisi air dengan efisien. Pengujian dilakukan dengan dua objek water truck berkapasitas 1000 ml dan 500 ml dengan durasi pengisian masing-masing 9 detik dan 5 detik. Sistem ini juga dilengkapi dengan mekanisme monitoring yang ditampilkan pada display dan indikator pengisian penuh menggunakan buzzer. Pengukuran dan pengujian menunjukkan persentase kesalahan pada komponen baterai sebesar 27% dibandingkan datasheet, namun komponen lainnya berada dalam rentang yang sesuai. Efektivitas panel surya diuji dengan daya puncak 5,5 watt pada kondisi cerah. Pengujian baterai selama 120 menit menunjukkan Depth Of Discharge sebesar 42%, menjaga umur baterai dengan baik. Sistem otomatis ini dapat meningkatkan efisiensi operasional dan mengurangi risiko keselamatan akibat pengisian manual. Penelitian ini memberikan kontribusi penting dalam penerapan teknologi otomatisasi di industri pertambangan. Kata kunci — Efisiensi Pengisian Air; Sensor Inframerah; Sensor Ultrasonik; Sistem Otomatis; Water Truck.